2020
DOI: 10.3389/fpls.2020.00539
|View full text |Cite
|
Sign up to set email alerts
|

Genomic Selection Using Pedigree and Marker-by-Environment Interaction for Barley Seed Quality Traits From Two Commercial Breeding Programs

Abstract: With the current advances in the development of low-cost high-density array-based DNA marker technologies, cereal breeding programs are increasingly relying on genomic selection as a tool to accelerate the rate of genetic gain in seed quality traits. Different sources of genetic information are being explored, with the most prevalent being combined additive information from marker and pedigree-based data, and their interaction with the environment. In this, there has been mixed evidence on the performance of u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 48 publications
2
7
0
Order By: Relevance
“…This gain is not surprising and may be due to the significant contribution of variance components contributed by the interaction effects. Thus, we argue that reasonable gains in the prediction ability can be achieved by jointly considering the main and environmental interaction components as depicted in previous studies on wheat (Burgueño et al, 2012;Sukumaran et al, 2017) and barley (Ankamah-Yeboah et al, 2020).…”
Section: Pedigree Information To Accesses Predictionssupporting
confidence: 61%
See 1 more Smart Citation
“…This gain is not surprising and may be due to the significant contribution of variance components contributed by the interaction effects. Thus, we argue that reasonable gains in the prediction ability can be achieved by jointly considering the main and environmental interaction components as depicted in previous studies on wheat (Burgueño et al, 2012;Sukumaran et al, 2017) and barley (Ankamah-Yeboah et al, 2020).…”
Section: Pedigree Information To Accesses Predictionssupporting
confidence: 61%
“…In general, the incorporation of genotype-byenvironment interactions (pedigree-by-environment; A × E here) in prediction models increased the predictive ability in all three scenarios. Dissecting and quantifying A × E has been an integral part of predictions and has led to increased prediction ability (Jarquín et al, 2017;Ankamah-Yeboah et al, 2020), as found in this study. Further models, involving the GCA and SCA effects along with the A × E interactions have slightly better predictive ability as compared to those only involving the GCA and SCA effects.…”
Section: Pedigree Information To Accesses Predictionsmentioning
confidence: 69%
“…Notwithstanding, it should be mentioned that the pedigree-assisted models including phenotypic observations from preliminary yield trials performed sometimes similar or even superior to the corresponding genomic-assisted selection model. This observation was likewise made by the authors of [15,17] when predicting already tested lines across a multitude of international mega-environments, and might be attributed to the ability to differentiate between lines within families if preexisting information of the selection candidates is exploited for making predictions. Further possible influencing factors include the altering of performance rankings by inducing a shrinkage towards family means when modelling covariances between family members [48] as well as the previous mentioned drawing of performance information from half-sibs and full-sibs [49,50].…”
Section: Discussionmentioning
confidence: 61%
“…Two reasonable explanations as to why the GBLUP method outperformed the proposed deep learning method even with the proposed calibration method could be that the four data sets are: 1) small and, as pointed out above, the deep learning methods are data hungry, and 2) they do not have complex nonlinear patterns. It is also important to highlight that our results only used markers (not pedigree) information, whereas some researchers have reported similar results using both pedigree and markers (Ankamah-Yeboah et al, 2020;Calleja-Rodriguez, et al, 2020). Furthermore, the training process with the two deep learning methods (DL_M1 and DL_M2) was considerable slower than the conventional GBLUP method.…”
Section: Discussionmentioning
confidence: 62%